(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
BeautyFull salon will be established to fulfill the needs and wants of the customer. Everybody wants to look beautiful; beauty needs maintenance and care that can be best provided by a professional. However, going to BeautyFull Salon can provide many benefits that you cannot get at your normal salon; we offer also food. Hence, you should not hesitate and put off taking care of your appearance. BeautyFull Salon will relieve you from stress. With busy lives people lead today, such as career, children, school, and managing household duties, opportunities for rest and recreation should not be missed. This study used a descriptive research method. The researchers surveyed to know if the BeautyFull Salon is accessible, if the prices of products and services offered are affordable, if the product offered with a twist would be acceptable to the customer, and if BeautyFull Salon offers a good promotion. The researchers included 50 respondents composed of employed, unemployed, self-employed, and students. This study also utilized financial statements in identifying the feasibility of the business. The results of the survey showed that 30% of the respondents said that BeautyFull Salon is accessible and easy to go. Most of the respondents can afford the price of the services and the product offered. Respondents said that the products offered with are acceptable with a twist and BeautyFull Salon have good strategies to gain more customer. The financial aspect of this study showed that the business is profitable and can generate enough revenue. Despite the high entry in starting the business, the return on investment of the business will increase 19% on its first year of operation and will continually increase on the following year of its operation. The researchers recommended that BeautyFull Salon can compete with other competitors, and it also gives high quality and good services to satisfy the customer. BeautyFull Salon will be more productive and much profitable to have another branch not only in Quezon City.